2019
DOI: 10.1037/fam0000494
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ child-related schemas: Associations with children’s asthma and mental health.

Abstract: The parent–child relationship, a key dyad of the family, can influence disease-related and psychological processes in children with asthma. Although the critical role of parenting behaviors in asthma outcomes is well established, less is known about the attitudes and beliefs underlying parents’ interactions with their children and how those attitudes may relate to asthma outcomes. Thus, this study aimed to identify profiles of parents’ schemas pertaining to their children with asthma and examine whether child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The parent's speech was audio‐recorded, and later coded by a professional coder at another university, with Dr. Bullock serving as the master coder. We focused on criticism, based on 6 items (parent is critical of child behavior or traits, makes negative comments about the relationship with child, uses negative humor or sarcasm, assumes or attributes negative intentions to child, reports conflicts with child; Bullock & Dishion, 2007 ; Greenlee et al., 2019 ; Smith et al., 2013 ; Waller et al., 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…The parent's speech was audio‐recorded, and later coded by a professional coder at another university, with Dr. Bullock serving as the master coder. We focused on criticism, based on 6 items (parent is critical of child behavior or traits, makes negative comments about the relationship with child, uses negative humor or sarcasm, assumes or attributes negative intentions to child, reports conflicts with child; Bullock & Dishion, 2007 ; Greenlee et al., 2019 ; Smith et al., 2013 ; Waller et al., 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…FAARS captures two dimensions of the parent’s narrative: criticism and warmth. We focused on parental criticism, or a negative relational schema, an implicit negative representation of the child and the parent–child relationship (Bullock & Dishion, 2007; Greenlee et al, 2019; Smith et al, 2013). Criticism is based on six items (parent is critical of child behavior or traits, comments on the negative relationship with child, uses negative humor or sarcasm, assumes or attributes negative intentions to child, reports conflict with child).…”
Section: Methodsmentioning
confidence: 99%
“…The coding targets the implicit and explicit aspects of the cognitive and emotional content, thus aligning well with the construct of IWMs as informed by attachment theory. Because of our interest in negative, hostile IWMs as linking parents’ insecurity to their power assertion, we focused on parental criticism, or a negative relational schema, an implicit negative attitude, which specifically captures a negative representation of the child and the parent–child relationship (Bullock & Dishion, 2007; Greenlee et al, 2019; Smith et al, 2013).…”
mentioning
confidence: 99%
“…70 In regard to early environmental influences, several recent parenting studies have shown that highly critical and over-protective parenting may explain the higher level of anxiety in children with asthma. 71,72 However, these studies have been carried out in small parent-child dyad populations and require further research.…”
Section: F I G U R Ementioning
confidence: 99%